Effect of pruning intensity on biomass and essential oil yield in wild paramela (Adesmia boronioides Hook f.) - Nagahama, Nicolás; González, Silvia Beatriz; Grech, Marta Gladys; Retta, Daiana Sabrina (Elsevier, 2025)
Adesmia boronioides Hook. f. (known as paramela), a member of the Fabaceae family, is native to Argentinean and Chilean Patagonia. Its leaves and young stems are used in the traditional health care system of these countries to treat rheumatic pains, colds, digestive disorders, and respiratory congestion. Paramela presents excellent organoleptic qualities and is attracting growing commercial interest. In recent years the gathering of plant material from natural populations for the extraction and export of essential oils has increased; however, no studies exist on harvest management for this species. In this study plants from a natural A. boronioides population underwent three different pruning treatments (light, medium and heavy) and their response in biomass production and the yield and quality of their essential oils was evaluated over four consecutive years. Of the different pruning intensities, the medium level generated the greatest amount of biomass for all years (p< 0.001) even though the increase seen in production up to the third harvest was followed by a marked decrease. By applying a medium pruning level for two consecutive years on the same plants, we achieved up to 112 % more biomass and 116 % higher essential oil yield compared to the initial pruning. Under the heavy pruning treatment 10 % of the plants died after the second consecutive pruning. Furthermore, we compared the yield and qualitative characteristics of essential oils (EO) over the first three years under the medium pruning level. We observed that EO yields increased after successive pruning, but the chemical compositions (GC-FID-MS) were not significantly affected in the years evaluated. These results provide valuable information for the design of sustainable harvesting protocols for A. boronioides and indicate ways to improve the yield in biomass and essential oils from wild populations.